Exosomal Transfer From Human Renal Proximal Tubule Cells To Distal Tubule And Collecting Duct Cells - Gildea, John J. (Clin Biochem, 2014)
OBJECTIVES: Exosomes are 50-90 nm extracellular membrane particles that may mediate trans-cellular communication between cells and tissues. We have reported that human urinary exosomes contain miRNA that are biomarkers for salt sensitivity and inverse salt sensitivity of blood pressure. This study examines exosomal transfer between cultured human renal proximal tubule cells (RPTCs) and from RPTCs to human distal tubule and collecting duct cells. DESIGN AND METHODS: For RPTC-to-RPTC exosomal transfer, we utilized 5 RPTC lines producing exosomes that were fluorescently labeled with exosomal-specific markers CD63-EGFP or CD9-RFP. Transfer between RPTCs was demonstrated by co-culturing CD63-EGFP and CD9-RFP stable clones and performing live confocal microscopy. For RPTC-to-distal segment exosomal transfer, we utilized 5 distal tubule and 3 collecting duct immortalized cell lines. RESULTS: Time-lapse videos revealed unique proximal tubule cellular uptake patterns for exosomes and eventual accumulation into the multi-vesicular body. Using culture supernatant containing exosomes from 3 CD9-RFP and 2 CD63-EGFP RPTC cell lines, all 5 distal tubule cell lines and all 3 collecting duct cell lines showed exosomal uptake as measured by microplate fluorometry. Furthermore, we found that RPTCs stimulated with fenoldopam (dopamine receptor agonist) had increased production of exosomes, which upon transfer to distal tubule and collecting duct cells, reduced the basal reactive oxygen species (ROS) production rates in those recipient cells. CONCLUSION: Due to the complex diversity of exosomal contents, this proximal-to-distal vesicular inter-nephron transfer may represent a previously unrecognized trans-renal communication system.